(untitled) (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2023)
This research was motivated by the author’s interest in the uniqueness of the Ngrowot Fasting Tradition at Darul’Ulum Islamic Boarding School, which is currently still carrying out the tradition even in this modern era. The research approach that the author uses is descriptive qualitative with a field research. This study used data collection techniques, namely: Observation (observation), interviews, and documentation. The results of this study found that ngrowot fasting is an acculturation between Islam and Javanese culture, the form of its implementation is to refrain from eating food derived from rice. The duration of the implementation is at least one year with the condition that you have received a diploma from the Kyai directly. Ngrowot fasting provides many benefits and good impacts for the perpetrators, including: it can provide peace of mind because you are always grateful and change your behavior for the better, and make it easier to receive the knowledge given by ustadz and ustadzah. The perpetrators of the Ngrowot fast interpret the Ngrowot fast as a form of penance and concern that can train the ascetic soul to reduce worldly pleasures. Ngrowot fasting which is carried out at Islamic boarding schools does not deviate from the teachings of Islam even though it is not a sunnah fasting in Islam but the diploma, intention and practice are in accordance with Islamic religious law. Finally, the author recommends to santri and female students to always preserve the Ngrowot fasting tradition and intend it because they hope for the blessing of Allah SWT.